2006
DOI: 10.1021/op050232o
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ammonium Chloride as an Effective Promoter of the Asymmetric Hydrogenation of a β-Enamine Amide

Abstract: An investigation into the cause of substrate specific hydrogenation performance variability was conducted. A significant and unexpected correlation was observed between apparent pH of a solution of the substrate and rate of conversion and enantioselectivity. This observation led to the examination of low and variable levels of native ammonium chloride in different lots of substrate. The presence of ammonium chloride was found to have a positive effect on reaction rate and enantioselectivity when controlled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 8 publications
0
23
0
2
Order By: Relevance
“…Many publications appeared treating the problem of the synthesis of this compound and its derivatives. For instance, a scheme of asymmetric synthesis of the sitagliptin phosphate from the precursor, α,β-enamine amide, is given in [ 152 ]. A wide search for effective antidiabetic agents was performed among the homologues of this compound; therewith the varied structural parameter was the substituent in the phenyl ring [ 153 ] and also the substituents in the piperazine fragment [ 154 ].…”
Section: Antidiabeticsmentioning
confidence: 99%
“…Many publications appeared treating the problem of the synthesis of this compound and its derivatives. For instance, a scheme of asymmetric synthesis of the sitagliptin phosphate from the precursor, α,β-enamine amide, is given in [ 152 ]. A wide search for effective antidiabetic agents was performed among the homologues of this compound; therewith the varied structural parameter was the substituent in the phenyl ring [ 153 ] and also the substituents in the piperazine fragment [ 154 ].…”
Section: Antidiabeticsmentioning
confidence: 99%
“…Commercial manufacture of the drug substance involves an enantioselective hydrogenation of an unprotected b-enamine amide 131 (Scheme 29.6). 191 It was shown that asymmetric hydrogenation of 131 can carried out at 50 C in methanol in the presence of chiral Rh (I)-catalysts prepared from [Rh(COD)Cl] 2 and Josiphos SL-J002-1 ligand (Solvias) under 100 psig (or 115 psi) of H 2 -pressure to achieve 82-99% conversions in to chiral amine 132 with enantioselectivity ranging from 89% to 95% ee. 191 Further extensive screenings on a search for the most suitable catalyst for the highly enantioselective hydrogenation of 131 provided in collaboration with Solvias revealed that also other ligands, even ones outside the ferrocenyl structural class, could effect this transformation with high enantioselectivity.…”
Section: Rhodium-catalyzed Stereoselective Hydrogenation Of Functionamentioning
confidence: 99%
“…Subsequent recrystallization and salt formation with phosphoric acid gave Januvia® (sitagliptin phosphate, 8 ). Efforts to optimize efficiency and examine the mechanism of the asymmetric process revealed a reactivity and selectivity dependence on the pH of the reaction solution 39. It was found that ∼1 mol% of a mild acid (i.e., ammonium chloride) was essential for the reaction to proceed reproducibly on large scale.…”
Section: β-Enamino Amide Hydrogenations – Januvia®mentioning
confidence: 99%